Larva migrans - A cutaneous presentation in a tourist - Alves, Conceição (2012)
LARVA MIGRANS - A CUTANEOUS PRESENTATION IN A TOURIST Cutaneous larva migrans is the most common dermatosis diagnosed among tourists returning from tropical areas to tem- perate regions. In most developed countries, cases are imported. We report the case of a 31-year-old woman who visited her family doctor because of an erythematous, serpiginous, prurit- ic lesion on the dorsum of her foot, that began three months previously, after returning from a visit to Jamaica. These clinical and epidemiologic features facilitated the diagnosis of cutaneous larva migrans infection. The patient was treated with alben- dazole, with complete recovery of the lesion. Although rarely diagnosed in primary health care in Portugal, this disease should be included in the differential diagnosis of cutaneous lesions found in tourists, given the increase in travel to tropical regions.